0010 The safest R.I.D.E (restrained, in the back, day and night, every time). (26th April 2015) - Alonso, Julie; Peters, Marla; Williams, Kathy
Abstract : Statement of purpose: If in a crash, children under age 13 riding in the front seat are 50% more likely to be killed or seriously injured than children riding in the back seat (WA Traffic Safety Commission data). Washington law requires children under age 13 to ride in the back seat whenever practical to do so. Despite our strong child passenger safety laws and a well-developed statewide child passenger safety program, child passenger restraint use rates remain relatively low. This session demonstrates the use of observational data to create a focused educational and enforcement intervention at elementary schools to improve child passenger safety. Methods/Approach: Observational surveys during morning drop-off at 16 elementary school showed approximately one in five children were illegally seated in the front seat. In partnership with law enforcement, four Safe Kids Coalitions conducted a four-week long educational and enforcement campaign at local schools. The Campaign included observational surveys, a letter home, classroom visits, media blasts, and campaign messaging at schools and in the community. A statewide parent survey was done by Safe Kids Washington to determine why children under age 13 were riding in the front seat. Results: Results are coming in and will be shared at the Safe States Annual Meeting. Conclusions: We are now in phase one. Early results show an improved rate of children riding in the back seat. The campaign will continue through June 2015. Results from phase one, including the parental survey data, will be used to inform phase two, which will have an added focus on booster seat use into 2016. Significance and contribution to the field: Washington State has one of the strongest child passenger safety laws in the country. In our intervention development, we discovered few states have programs focused specifically on keeping children riding in the back seat, despite evidence that it reduces the rate of serious injury and death by half. Our approach of using state and local partnerships, research, data, education, and enforcement to help change risk behaviour is a good model for others to adapt or adopt in their community.